STUDI KELAYAKAN BISNIS PENDIRIAN USAHA BOLEN PISANG KENCANA - Majid, Muhammad Ilham; Maryono, Dicky (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2025)
This study analyzes the feasibility of the Bolen Pisang Kencana culinary business in Bandung City. The background of the study is based on the potential of bananas as the largest fruit commodity in Indonesia and the public trend of liking local, halal, and handmade processed products. The method used is a business feasibility study by reviewing market, marketing, production, human resources, finance, environment, legal, and SWOT aspects. The results of the study indicate a broad market opportunity with relatively small initial capital supported by affordable prices and distinctive flavors. From the financial aspect, the business is declared feasible to run with an NPV of IDR 53,068,879, an IRR of 57.49%, a PI of 8.36, a Payback Period of 1.90 years, and a sharp increase in ROI from 2.07% in the first year to 101.29% in the 5th year, reflecting significant profit growth and investment efficiency. The environmental aspect shows small and easily managed production waste, while the legal aspect confirms the owner's commitment to completing business permits (NIB, PIRT, and halal). The SWOT analysis highlights the strengths of quality products and competitive pricing, weaknesses in digital marketing and legality, opportunities from Bandung's culinary trends, and threats from competition and fluctuating raw material prices. Overall, this business is feasible to develop, both financially and non-financially, with key strategies including improving legality, optimizing digital marketing, and product innovation.